Identification of a New Siderophore Acinetoamonabactin Produced by a Salt‐Tolerant Bacterium Acinetobacter Soli. Issue 28 (26th July 2018) - Mudhulkar, Raju; Rajapitamahuni, Soundarya; Srivastava, Sakshi; Bharadwaj, Satyavolu V. Vamsi; Boricha, Vinod P.; Mishra, Sandhya; Chatterjee, Pabitra B.
Abstract: A halotolerant bacterium Acinetobacter soli (MTCC 5918), isolated from the salt farm of our institute, was found to secrete a novel siderophore under iron deprivation conditions. A combination of multinuclear one and two dimensional NMR spectroscopies in conjunction with mass technique revealed that the siderophore, we named acinetoamonabactin (1), is a triscatechol derivative of tris(aminomethyl)methylamine. Abstract : A salt‐tolerant bacterium Acinetobacter soli (MTCC 5918), isolated from the saltpan of CSIR‐CSMCRI, was found to produce a novel siderophore acinetoamonabactin under iron‐starvation condition. Multinuclear 1D ( 1 H and 13 C) and 2D (COSY, HSQC, and HMBC) NMR and mass spectroscopies established the molecular structure of the novel siderophore. The siderophore, we named acinetoamonabactin, is a triscatechol derivative of tris(aminomethyl)methylamine and it binds Fe 3+ stoichimetrically with an association constant K=1.7x10 12 M −1 .